Early exit from ECB bond purchase program could reduce GDP growth and inflation - Marius Clemens; Stefan Gebauer; Malte Rieth (DIW Economic Bulletin, 2017)
The European Central Bank is planning a gradual reduction of government bond purchases under the asset purchase program it initiated in 2015. The present study by the German Institute for Economic Research analyzes the potential macroeconomic implications of different exit strategies. The authors examined the potential effects of a reduction in net purchase volume, an early exit, and a faster exit from the program on output and inflation in the euro area. Model simulations showed that economic growth and inflation rates would decrease in all three scenarios. However, the effects of the scenario with reduced asset purchases are less severe than those of an exit from the program that is earlier or faster than expected. In particular, an early exit from the program should significantly affect inflation rates, an effect that the European Central Bank should factor into its decision-making process.
Keywords: E4; E52; E58; 330; Tapering; Quantitative Easing; Monetary Policy